Anti-Restriction Gene Homologs Are Highly Represented in Methicillin-Resistant and Multidrug-Resistant Staphylococcus aureus ST239 and ST398: Implications for Resistance Gene Acquisitions - Deborah Nascimento Santos Silva; Cristiana Ossaille Beltrame; Ana Maria Nunes Botelho; Caroline Lopes Martini; Matheus Assis Côrtes Esteves; Isabella Alvim Guedes; Laurent Emmanuel Dardenne; Agnes Marie Sá Figueiredo (MDPI AG, 2022)
Multidrug resistance is commonly acquired by transferring DNA from one bacterium to another. However, the mechanisms that enhance the acquisitions of foreign genes are poorly understood, as well as the dynamics of their transmission between hosts in different environments. Here, genomic approaches were applied to evaluate the enrichment of the S. aureus chromosome with resistance traits in groups of genomes with or without anti-restriction genes and to analyze some evolutionary aspects of these acquisitions. Furthermore, the role played by an anti-restriction gene in improving multiresistance in MRSA was investigated by molecular cloning. A strong association was observed between the presence of anti-restriction gene homologs and patterns of multidrug resistance. Human isolates, mainly ST239-SCCmecIII, carry ardA-H1, and from animal sources, mainly CC398, carry ardA-H2. Increased DNA transfer was observed for clones that express the ardA-H1 allele, corroborating its role in promoting gene transfer. In addition, ardA-H1 was expressed in the dsDNA format in the BMB9393 strain. The evolution of successful multidrug-resistant MRSA lineages of the ST239 and ST398 was initiated not only by the entry of the mec cassette but also by the acquisition of anti-restriction gene homologs. Understanding the mechanisms that affect DNA transfer may provide new tools to control the spread of drug resistance.